Using landing statistics and fishers' traditional ecological knowledge to assess conservation threats to Pacific goliath grouper in Colombia. Issue 2 (24th January 2018) - Castellanos‐Galindo, Gustavo A.; Chong‐Montenegro, Carolina; Baos E, Rodrigo A.; Zapata, Luis A.; Tompkins, Paul; Graham, Rachel T.; Craig, Matthew
Abstract: Groupers are vulnerable to fishing pressure largely because of their life‐history traits. The Pacific goliath grouper (PGG; Epinephelus quinquefasciatus ), the largest reef fish inhabiting the tropical Eastern Pacific region, is suspected to be subject to high levels of exploitation, but scarce information exists on their population status and the species remains classed as Data Deficient according to the International Union for Conservation of Nature (IUCN) Red List. This study documents for the first time the threats to the PGG along the Colombian Pacific coast, where one of the few active fisheries for this species persists. Reconstructed landings of groupers and traditional ecological knowledge, gathered throughout several coastal villages, were used to obtain a historical and contemporary overview of the PGG status in Colombia. Over the past 20 years grouper landings in the Colombian Pacific have been around 200 tons per year. Landings of PGG have averaged ~35 tons per year and are now close to matching those of the historically most landed grouper on this coast, the rooster hind ( Hyporthodus acanthistius ). The current small‐scale fishery for PGG focuses on immature small individuals, with most taken from the extensive southern mangroves. Until recently fishers have captured PGG exclusively with handlines, but new fishing practices (spearfishing) and markets commanding higher prices for small individuals are increasing the extinction risk for the PGG. The exploitation of PGG in the Colombian Pacific may not be as severe as in other countries where severe population declines are suspected (e.g. Mexico). Low coastal human population density and the presence of relatively intact mangroves, essential habitat for juvenile fishes, contribute to the persistence of PGG populations throughout the Colombian Pacific. National and regional conservation and management measures should identify and protect mangrove nurseries and offshore spawning aggregation sites. Well‐enforced protected nurseries and spawning aggregation sites will then protect juvenile and adult PGG, improving the sustainability of this fishery.